Reversible Suppression of Fear Memory Recall by Transient Circadian Arrhythmia - Steiger, Athreya; Farfan, Julia; Fisher, Nathan; Heller, H. Craig; Fernandez, Fabian-Xosé; Ruby, Norman F. (Frontiers in Integrative Neuroscience, 2022)
We tested the hypothesis that a temporary period of circadian arrhythmia would transiently impair recall of an aversive memory in Siberian hamsters (Phodopus sungorus). Unlike mice or rats, circadian arrhythmia is easily induced in this species by a one-time manipulation of their ambient lighting [i.e., the disruptive phase shift (DPS) protocol]. Hamsters were conditioned to associate footshocks with a shock chamber (context) and with a predictive auditory tone (cue), and then exposed to the DPS protocol. Following DPS, animals either became arrhythmic (ARR), reentrained to the light-dark cycle (ENT), or became arrhythmic for < 14 days before their circadian locomotor rhythms spontaneously recovered and reentrained (ARR-ENT). Tests for contextual memory showed that freezing was decreased 9–10 days post-DPS when both ARR and ARR-ENT groups were arrhythmic. Once ARR-ENT animals reentrained (day 41), however, freezing was elevated back to Pre-DPS levels and did not differ from those observed in ENT hamsters. ENT animals maintained high levels of freezing at both time points, whereas, freezing remained low in ARR hamsters. In contrast to contextual responses, cued responses were unaffected by circadian arrhythmia; all three groups exhibited elevated levels of freezing in response to the tones. The differential impact of circadian arrhythmia on contextual versus cued associative memory suggests that arrhythmia preferentially impacts memory processes that depend on the hippocampus.